Comparison of external load on high speed actions in friendly macth and training sessions (Comparación de carga externa en las acciones de alta velocidad en paridos amistosos y sesiones de entrenamientos) - Francisco Javier Toscano Bendala; Miguel Angel Campos Vázquez; Luis Jesús Suarez-Arrones; Francisco Javier Núñez Sánchez (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The aim of the current research was to find out the differences that exist between the external load in high-velocity actions (SP+) in competitions and in training sessions of professional soccer team. We took as SP+ indicators those actions that the soccer players performed over 23 km·h-1 and could be held for at least 1 second. It was monitored 25 professional players belonging to the first team of a team of the first Spanish soccer division, and were used 10 GPS devices were used (SPI, ELITE model, GPSport, Canberra, Australia). These GSPORT transmitters have a sampling frequency of 1 Hz. The results of our study showed how during the game, the players performed substantially more number of SP+ de 1 s, 2 s, 3 s y 4 s (per minute of activity) than during training.